Managing tropical forests for the future - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Unless timber can be harvested in a sustainable manner tropical forests, and their associated flora and fauna, will not survive. The conservation of the tropical forest has become an international issue, and its sustainable utilization is high on...